2006
DOI: 10.1103/physrevb.74.012411
|View full text |Cite
|
Sign up to set email alerts
|

Spin dynamics inFe2O3TeO2glass: Experimental evidence for an amorphous oxide spin glass

Abstract: We have examined spin dynamics including magnetic aging and memory effects as well as critical slowing down for 20Fe 2 O 3 · 80TeO 2 ͑mol %͒ glass. Scaling analysis on critical slowing down reveals that the present glass exhibits a critical behavior as observed in a prototype of spin glasses. Aging and memory effects peculiar to spin glasses have been observed in the magnetically ordered phase of the present glass. These experimental results strongly confirm that the 20Fe 2 O 3 · 80TeO 2 glass is converted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 29 publications
3
36
0
Order By: Relevance
“…Hence, the superparamagnetic or cluster spin glass-like behaviour may affect the magnetic transition. To clarify thoroughly the mechanism of magnetic transition observed for Fe 2 O 3 -TeO 2 glasses, further measurements such as temperature dependence of non-linear susceptibility are required as described below, although our recent study of spin dynamics on the Fe 2 O 3 -TeO 2 glass with 20 mol% of Fe 2 O 3 undoubtedly confirms that the glass becomes a spin glass phase at very low temperatures [20]. Fig.…”
Section: Fe 2 O 3 -Teo 2 and Mno-teo 2 Glassesmentioning
confidence: 93%
“…Hence, the superparamagnetic or cluster spin glass-like behaviour may affect the magnetic transition. To clarify thoroughly the mechanism of magnetic transition observed for Fe 2 O 3 -TeO 2 glasses, further measurements such as temperature dependence of non-linear susceptibility are required as described below, although our recent study of spin dynamics on the Fe 2 O 3 -TeO 2 glass with 20 mol% of Fe 2 O 3 undoubtedly confirms that the glass becomes a spin glass phase at very low temperatures [20]. Fig.…”
Section: Fe 2 O 3 -Teo 2 and Mno-teo 2 Glassesmentioning
confidence: 93%
“…Spin glass (SG)-like magnetic transition of oxide and fluoride glasses has been extensively investigated so far [1][2][3][4][5][6]. In most insulating oxide and fluoride glasses, short-range antiferromagnetic (AFM) superexchange interactions via anions are dominant, as demonstrated by the negative values of Weiss temperature (θ W ) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there are few experiments concerning spin dynamics of magnetically ordered phases. Recently we have demonstrated that 20Fe 2 O 3 Á 80TeO 2 (mol%) glass exhibits the spin dynamics involving magnetic aging and memory effects as well as critical slowing down as observed in archetypal spin glasses [8]. In the present investigation, we have carried out experiments relevant to the magnetic aging and memory effects in magnetically ordered phase of 32Fe 2 O 3 Á 48Bi 2 O 3 Á 20B 2 O 3 (mol%) glass prepared by using a conventional melt-quenching method.…”
mentioning
confidence: 98%
“…Below spin glass transition temperature, magnetic moments are frozen in such a manner that the direction of each of the magnetic moments is randomly oriented, but it takes an infinite time to reach a thermodynamic equilibrium state. Experimental, theoretical, and numerical approaches have been carried out to clarify the spin dynamics in the spin glass phase such as magnetic aging phenomena involving rejuvenation and memory effects [3][4][5][6][7][8], although these phenomena are not completely understood yet.Amorphous phases of ionic compounds such as oxide and fluoride glasses containing a large amount of magnetic ions are a prototype of a solid in which magnetic moments are randomly distributed. Several investigators reported that oxide glasses containing a large amount of magnetic ions show magnetic transitions as observed in spin glasses or superparamagnets [9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation